1984
DOI: 10.1097/00000658-198412000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Computerized 24-hour Ambulatory Esophageal pH Monitoring and Esophagogastroduodenoscopy in the Reflux Patient

Abstract: Ambulatory 24-hour esophageal pH monitoring and esophagogastroduodenoscopy were performed in 72 patients with symptoms suggestive of gastroesophageal reflux. Additionally, 22 asymptomatic healthy volunteers underwent pH monitoring. In patients with classic reflux symptoms and endoscopic esophagitis, a mean of 5.41 minutes/hour of reflux below pH 4 was found compared to 0.70 minutes/hour in controls (p less than 0.0001). The mean number and duration of reflux events in this group were 1.51 events/hour and 4.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…Normal values for control subjects undergoing conventional catheterbased pH monitoring were used to determine whether oesophageal acid exposure was normal. [7][8][9][10][11][12][13][14] Representative tracings obtained from the Bravo capsule are illustrated in Figures 3 and 4. Six patients also underwent colonoscopy during the same endoscopic session, four (67%) of whom had positive tests.…”
Section: Resultsmentioning
confidence: 99%
“…Normal values for control subjects undergoing conventional catheterbased pH monitoring were used to determine whether oesophageal acid exposure was normal. [7][8][9][10][11][12][13][14] Representative tracings obtained from the Bravo capsule are illustrated in Figures 3 and 4. Six patients also underwent colonoscopy during the same endoscopic session, four (67%) of whom had positive tests.…”
Section: Resultsmentioning
confidence: 99%
“…(b) EAE may be underestimated. Concerns about sensitivity are highlighted by the observation that as many as 23% of patients with endoscopically detected esophagitis may demonstrate distal EAE values that fall within the normal range [70]. Many other studies have reported high sensitivities for pH monitoring that approximate 90% for erosive esophagitis (EE) patients, while the sensitivity of pH monitoring in patients with NERD is significantly lower, raising questions as to how to best define GERD in the absence of erosions [71].…”
Section: Better Understanding Of the Precise Role Of Acid In Nerdmentioning
confidence: 99%
“…Our laboratory results of [23] have shown that even in clearly existing primary reflux disease (e.g., esophagitis without other disease) it was not possible to prove pathological reflux by pH monitoring in 18% of the cases. Vitale et al [21] published similar results. In a group of patients with suspected esophagitis, they did not find a pH metrical correlate in 8 of 40 patients with endoscopically proved esophagitis.…”
Section: Phase 3 Studiesmentioning
confidence: 57%